Observations on certain aspects of ecology of selected rivers in Nagaland State, India - Gurumayum, S. D.; Daimari, P.; Goswami, B. S.; Choudhury, M. (Indian Journal of Fisheries, 2013)
Seasonal variations in physico-chemical parameters of water and soil, abundance and quality composition of plankton, periphyton and benthos were investigated during the period 2000-2001 in six rivers of Nagaland viz ., Doyang, Dikhu, Tserang, Sidzu, Tezu and Zungki. Plankton, periphyton and benthos population fluctuated between 18-282 ul -1 , 13100-180500 u cm -2 and 159-508 nos. m -2 respectively. Dissolved oxygen, free carbondioxide, alkalinity, specific conductivity, total dissolved soilds, chloride, total hardness, Ca, Mg, Silicate, total iron, nitrate, phosphate and dissolved organic matter were found within the normal ranges of tropical hill streams. Primary productivity was found to vary within the range 500-999 mg C m -3 day -1 . The observations revealed that the rivers are mostly non-stressed in nature and are free from common problems related with anthropogenic activities.